Pengaruh Konsentrasi Pasar Audit, Keahlian Komite, dan Kompleksitas Operasional terhadap Kualitas Audit - Anggi Meilinda; Ratna Anggraini; Hafifah Nasution (Jurnal Kendali Akuntansi, 2026)
This study examines the effects of audit market concentration, audit committee expertise, and operational complexity on audit quality among infrastructure firms listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The analysis was based on a quantitative research approach using secondary data extracted from published annual reports and financial statements. Applying purposive sampling criteria, the study obtained a sample of 34 firms, representing 102 firm-year observations. Audit quality was measured using the Earnings Surprise Benchmark (EBS), while the proposed hypotheses were tested through binary logistic regression. The findings reveal that audit market concentration has a significant negative effect on audit quality, indicating that a more concentrated audit market tends to reduce the likelihood of higher audit quality. Conversely, audit committee expertise and operational complexity do not exhibit significant effects on audit quality. These results suggest that competitive conditions within the audit market remain an important determinant of audit quality, whereas corporate governance characteristics and operational complexity alone are insufficient to explain variations in audit quality among infrastructure companies.